PENGARUH PENERAPAN SISTEM INFORMASI PENGELOLAAN KEUANGAN DAERAH, DAN PELATIHAN PENGELOLAAN KEUANGAN TERHADAP KUALITAS LAPORAN KEUANGAN PADA SKPD KOTA BANDA ACEH - Siti Ghaida Afifah; Said Muniruddin; Riha Dedi Priantana (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2021)
This research aims to examine the impact of the application from Regional Financial Arangement Information System (SIPKD),and financial management training to financial reports quality of Banda Aceh City regional work unit (SKPD). Method of collecting data, used a questionnaire technique. The samples number are 78 employees who prepare financial statements at SKPD in Banda Aceh City. Using purposive sampling method, the respondents were selected. This research applies a quantitative analysis method with this calculation process assisted by the Statistical Product and Service Solutions (SPSS) application program. The outputs obtained are, the application from Regional Financial Arangement Information System (SIPKD) had a effect but is not significant impact to financial reports quality of Banda Aceh City regional work unit (SKPD), whereas financial management training had a significant impact to financial reports quality of Banda Aceh City regional work unit (SKPD) financial statements